Melanoma: Staging and Follow-Up - Chryssoula Papageorgiou; Zoe Apalla; Sofia-Magdalini Manoli; Konstantinos Lallas; Efstratios Vakirlis; Aimilios Lallas (Mattioli1885, 2021)
Cancer staging is the process determining to which extent a cancer has spread and where it is located in the body. A thorough staging is of utmost importance, not only because it provides the most accurate prognostic estimation, but also because several crucial decisions, such as the treatment choice and the follow-up strategy, vary according to the tumor's stage. The current staging system for melanoma is based on the 8th edition of TNM classification issued by the American Joint Committee on Cancer (AJCC) in 2017. It includes a clinical and a pathological staging, both consisting of 5 stages (0-IV). The stage of a melanoma is determined by several factors, among which the Breslow thickness, the pathological presence or absence of ulceration in the primary tumor, the presence and the number of tumor-involved regional lymph nodes, the presence or absence of in-transit, satellite and/or microsatellite metastases, and the presence of distant metastases. Following melanoma diagnosis, an accurate medical workup, in line with the stage and the physical examination, should be performed. A continuous patient monitoring is fundamental to detect a potential relapse or a second primary melanoma and should be lifelong. However, there is still no universally adopted follow-up strategy program and different follow-up schemes have been suggested. Future prospective studies are needed to evaluate different follow-up protocols according to the adopted therapy, as novel recent therapies (targeted and immunotherapies) are being increasingly used.